Probiotics and Synbiotics as Potential Biotics in Gut Health-Promoting Nutrition - Stephanie Kartjito, Melissa; Faisal Umam, Aldo (Journal of Indonesian Specialized Nutrition, 2024)
Disorders of gut health can impact a variety of health problems, including the digestive system, immunity, and even mental health. The aim of this study was to investigate the potential of probiotics and synbiotics as potential biotics in nutrition to improve gut health. This study used qualitative research methods. The data collection technique for this is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that probiotics and synbiotics are potential biotics in nutrition that can improve intestinal health. Probiotics and synbiotics can help modulate the composition of the body's beneficial microbiota. In addition, it can help reduce levels of pathogenic bacteria and help reduce persistent inflation of the intestines, which can improve the balance of the body's beneficial microbiota